PENENTUAN JUMLAH SUHU YANG OPTIMAL KIPAS KONDENSOR TERHADAP LAJU PENDINGINAN PADA AC 1 PK - Mustaqim ,; Agus Wibowo; Yasin , (Engineering : Jurnal Bidang Teknik, 2010)
The purpose of this paper is to determine the best blade number on the l PK refrigeration .rate of "Changhong" air conditioner with various number of fan blades apptied.This paper examines the installation of "Changhong" indoor air conditioner with a 1 pK capacity by mixing fan blade number, which are 3, 4, and s blades, measured using the measuring tools, such as thermo-couple, tlrcrmo-laser, pressure gouge and ampere meter. Used as the substitution of a room, a cabin having 1,5 m3 uolumes is used to obtain the steady temperature. After it is siady (the moueients of mrasuring tools and temperature on the permanent room are minimal) the data are collected by each fan usageThe data collected in this papper is annlyzed using the refrigerator characteristics table R-22 to obiain ilu pressure and enthatply values on enclr fan. Entlntpy unrue is used to find out the refrigeration rate characteristics values of each fan.The conducted test to achieue the results of using ile condenser fan with 3 blades are mref = 0,069504 kg/s, Qe, = 13.80602 kW, Qk= 11,75043 Kw, RE = 198,635 kj/kg, COP = 16.51438. The result using the fan with 4 blades are mref = 0,073904 kg/s, Qe = 14.9084 kW, Qk = 12.4525 kW, RE = 201,77 kj/kg, COP = 17,83301. Whereas, for the 5_bladed fan, the results are mref = 0.072425 kg/s, Qe = 14.52415 Kw, Qk = 12.2033 kW, RE = 20,541 kJ/Kg, COP, = 17.37339.From the results of "Changhong" air conditioner with 1 PK capacity analysis, the best result is achieved by using the condenser fan with 4 blade.Keyword : fan blades, R-22, evaporator capacity, condensing Capacity refrigerator effect, COP